Proliferasi dan Etno-Nasionalisme daripada Pemberdayaan dalam Pemekaran Daerah di Indonesia - AGUSTINO, LEO; YUSOFF, MOHAMMAD AGUS (UI Scholars Hub, 2010)
This paper attempts to explain and examine the variation on amalgamation in Indonesia. The proliferation of provinces, districts, cities as well as the problems after the implementation of amalgamation are discussed in this paper. The central argument of this paper is that the amalgamating process is not only driven by purpose of amalgamation itself—e.g. to provide better public goods, public services and welfare of the people etc.—, but also driven by the role of elite actor(s). It is argued that the politics of identity used by elite actor(s) is an instrument to unite local people to support their desire to control power. Thus, to prevent the misunderstanding of the purpose of amalgamation, this paper provides practical suggestions to the case being examined.